(untitled) (Journal of the College of Basic Education, 2022)
The Symbolic Formation of Place and its Role in Aljawahiry’s Poetry Undoubtedly, place in modern literary studies is no longer the background within its frame the events of the text take place or just a reflection of the writer’s self itself. However, it goes further to be a formative factor among the most constituing ingredients of the text itself in specific or the literary work in general. Accordingly, place becomes a pivot in which literature theory is interested since it further contributes in forming the social entity and its cultural bases. Hence, Aljawahiry’s poetic text acquires variant symbolic dimensions not because it’s mere a place, yet for the widespread symbolic meanings it holds which are begotten by the serious events of the place itself around which the poet and other people’s positive and negative emotions are revolving. It extra formulates the collective understanding of the importance of place once it is violated. Consequently, place acquires its own value which influences all aesthetic and moral values that stir peoples.